Associations between specific components of executive control and eating behaviors in adolescence: A study using objective and subjective measures. (1st November 2020) - Nelson, Timothy D.; James, Tiffany D.; Nelson, Jennifer Mize; Johnson, Anna B.; Mason, W. Alex; Yaroch, Amy Lazarus; Espy, Kimberly Andrews
Abstract: A growing literature suggests that executive control (EC; also known as "executive functioning" or "EF") in adolescence may play an important role in the development of key health behaviors, including eating behaviors. However, existing literature has significant limitations in the conceptualization and measurement of EC. The current study aims to address these limitations by employing a multidimensional approach to conceptualizing and measuring adolescent EC, including both objective and subjective measures covering multiple components of EC, and examining links with specific eating behaviors. A community sample of adolescents (N = 208; mean age = 14.5 years) completed a battery of performance-based neuropsychological tasks assessing specific components of EC (i.e., working memory, inhibitory control, flexible shifting), a norm-referenced questionnaire covering problems with specific components of EC in daily life, and a measure assessing key eating behaviors (i.e., uncontrolled eating, emotional eating, cognitive restraint). Objectively-measured adolescent working memory was significantly and uniquely associated with cognitive restraint, with stronger working memory associated with less cognitive restraint. No other associations between performance-based EC tasks and eating behaviors were found. In contrast, using subjective reports of EC, problems with inhibitory control were associated with greater uncontrolled eating, and problems with flexible shifting were associated with greater emotional eating. The results suggest links between specific aspects of EC and specific eating behaviors in adolescence, as well as the potential importance of context for understanding the role of EC in eating behavior. Given evidence that EC is modifiable, the findings have potential implications for novel interventions addressing eating behaviors by targeting EC.